Strengthening palliative nursing care through integration of islamic educational values: An integrative review - Ghozali, Imam; Yusnita, Erni (School of Health Sciences Al-Ma'arif, 2026)
Background: Spiritual care is a core component in palliative nursing, but most of the literature still discusses it in a general framework and has not systematically integrated Islamic educational values as an ethical and professional foundation. Objective: Formulating a conceptual framework for strengthening palliative nursing care through the integration of Islamic educational values. Methods: The study used an integrative literature review design following the PRISMA flow. A systematic search was conducted on PubMed, Scopus, ScienceDirect, and Google Scholar for articles from January 2010–June 2025. The final search was conducted in June 2025 using a combination of the keywords “Islamic values,” “Islamic education,” “palliative nursing,” “palliative care,” and “spiritual care.” Of the 215 articles identified, 30 met the inclusion criteria after screening and full-text review. Analysis was conducted through thematic synthesis and quality assessment using the CASP and JBI checklists. Results: Four dominant core values were identified: rahmah (compassion), patience, sincerity, and trust (relief), with trust as a key determinant of professional ethics. Rahmah emerged most frequently and contributed to improved therapeutic communication, reduced anxiety, increased emotional support, and improved quality of life for terminally ill patients. The integration of these values also impacted patient satisfaction and strengthened nurse professionalism. Conclusion: The integration of Islamic educational values strengthens the ethical, spiritual, and professional dimensions of palliative nursing practice in a holistic and evidence-based manner. Further research using quantitative or mixed methods designs is needed to increase the generalizability of the findings.